Studentsâ Readiness to Implement Comprehensive Guidance and Counseling Services: a Preface for Improvement - Hidayat, RianRokhmad; makhmudah, Ulya (Sebelas Maret University, 2016)
Comprehensive guidance and counseling services (CGCS) was a complete framework in implementation ofguidance and counseling in school which was able to facilitate the students in facing the requirement of AsianEconomy Community (AEC). The readiness of the college students to implement CGCS need to bemeasured, as the preliminary research to see whether the students of FKIP UNS already had the knowledgeand skills to implement CGCS. This thing is important, because all this time college students who near tograduate still using the guidance and counseling curriculum focused on clinical, so that it was required âneedassessmentâ to arrange fine tuning workshop in order to be able to implement CGCS. The result ofidentification of the college studentsâ readiness perception profile to arrange and implement CGCS programthat systematic was 83%. The perception of college studentsâ readiness to arrange the program focused on thestudentsâ development was 92%. The perception of college studentsâ readiness to actively carry out thecollaboration and consultation with all the school staffs was 62%. The perception of college studentsâreadiness to create school environment which support the development of students was 68%. From those datawe can see, for the arrangement activity of systematic guidance and counseling program and focused on thestudentsâ development, the college students already had high level of readiness. That was considered as highscore, because in the lesson of candidates of guidance and counseling education in the FKIP UNS studyprogram already facilitated with subjects about preparation program. However the perception of readiness toimplement collaboration and consultation with all the school staffs and the readiness to create schoolenvironment which support the studentsâ development still low.